"It wasn't going to happen until I made it happen": World language teacher agency for multilingual advocacy. (October 2022) - Davis, William S.; Howlett, Kristina M.
Abstract: This article explores how multilingual teachers form and enact agency to advocate for multilingualism in a region where monolingualism is dominant. Grounded in an ecological perspective toward language teacher agency, this qualitative interview study analyzed how six American secondary world language teachers generated and enacted agency through the formation and implementation of a local multilingual advocacy initiative in an English-only state. Results of the analysis indicated that the world language teachers' sociopolitical beliefs about language, their identities and those of their students, and the urgency of language advocacy, in addition to the school and policy structures within which they worked, intensified their efforts to advocate for their students. Four themes were identified illustrating how the teachers engaged their agency for the purposes of multilingual advocacy: building relationships as bridges, pushing students, leveraging school administration, and working collectively. Implications for teacher education and future research in language teacher agency and multilingual advocacy are discussed.